Validity of Sale and Purchase Agreement Using Coin Flip System: A Perspective from Indonesian Civil Code and Islamic Commercial Law - Hakim, Danial Malikul; Al Munawar, Faishal Agil (PT. Riset Press International, 2025)
The Coin Flip system is an innovative method in sale and purchase agreements, where the price is determined by a coin toss. It is used when negotiations between the buyer and seller reach a deadlock, introducing a random element to the price determination, which differs from traditional methods. This study aims to analyze the validity of the Coin Flip system under both positive law (the Civil Code) and Islamic commercial law (fiqh muamalah). The focus is on whether the system meets the requirements for a valid agreement in the Civil Code and Islamic law. Additionally, the research examines the issue of maysir (gambling) involved in this system, which is crucial in sale agreements. The study employs a normative juridical method with a conceptual and legislative approach, utilizing primary, secondary, and tertiary legal sources. Data was collected through literature review and analyzed qualitatively. The findings show that the Coin Flip sale agreement is valid according to the Civil Code, as it satisfies both subjective and objective conditions, including a voluntary agreement between legally competent parties with a clear price and valid object. However, the system is not valid under fiqh muamalah, as it lacks a clear and definite price and includes elements of maysir (gambling), which is prohibited in Islam.